PENGARUH KOMUNIKASI DAN IKLIM ORGANISASI TERHADAP KINERJA DOSEN DI PERGURUAN TINGGI SWASTA DI MEDAN - JANNATUN NISA (JURNAL ILMIAH SIMANTEK, 2020)
The purpose of this study is to analyze the effect of communication between students and lecturers around private universities and organizational climate on the performance of private university lecturers in Medan. The method used is an explanatory survey. The population is the lecturer of private high school in Medan. Based on data analysis, there is information that: communication between students and lecturers has important meaning for lecturers' performance. By controlling other variables, the lecturers' performance significantly depends on the communication made with students, the organizational climate of the private tertiary institution has an important meaning for lecturers. By controlling for other variables, the lecturers' performance is significantly explained by the organizational climate of the private tertiary institution. The effective communication style developed by students is very effective when adjusted for lecturers who have low performance. While selling, participating, and delegating communication style is not effective if it is adjusted for lecturers who have low performance. Sales and participation style communication developed by students is very effective if it is adjusted for lecturers who have moderate performance. While the style of storytelling and delegating communication is not effective if it is adjusted for lecturers who have moderate performance. Delegating communication styles developed by students are very effective if adjusted for lecturers who have high performance. While telling, selling, and participating in communication style is not effective if it is adjusted for lecturers who have high performance. The results showed that the performance of lecturers as a frame of reference is an important factor in determining the effectiveness of communication between students and lecturers. In addition, research has placed organizational climate as an indicator that influences individual behavior in organizations.